Pengaruh Bentuk Latihan Fun Games Terhadap Ketepatan Smash Bolavoli - arianto0308, gustino; irawan, Roma; hermanzoni, hermanzoni; setiawan, yogi (Universitas Negeri Padang, 2021)
The problem in this study is the low achievement of volleyball athletes Delta Harapan Lunto Timur Sawahlunto city can be seen from the factors that affect the team's achievements, one of which is still the lack of accuracy when doing smashes. Population in this study was 20 men and 13 female volleyball athletes Delta Harapan Lunto Timur Sawahlunto City. Sampling by purposive sampling is a way of sampling. So the samples taken in this study as many as 12 volleyball athletes Delta Harapan Lunto Timur Sawahlunto City. The instruments in this study consisted of: variable Fun games (X) and precision Smash (Y) measured by conducting a test of accuracy Smash.Data analysis is done by using the formula t. test results from the analysis of data obtained: The results of the analysis obtained results from fungame exercises have a significant influence on the accuracy of smash in mark with the results obtained tcount = 9.5 > ttable = 1,812. Showing that there is an influence of fun games training form on the accuracy of smash volleyball athletes Delta Harapan Lunto Timur Sawahlunto city. Keywords: Fun games,smash,Physical Education,Play Method,volleyball